Le pirate informatique, un explorateur des courants juridiques du réseau - Primavera De Filippi; Mélanie Dulong de Rosnay (Tracés, 2014)
The article examines the figure of the computer pirate, its facets and its evolution under the influence of technical developments and the regulation thereof. The analysis is carried out by looking at the interplay between legal, technical and social norms, focusing on the relationship between new technologies bypassing the law and the rules of law which, while trying to regulate these new technologies, eventually extend into new and previously unregulated territories. From the first pirate radios to the peer-to-peer file haring platforms, a regularity can be found among the tensions and discrepancies that subsists between technical, and initially marginal innovations and the applicable law. Extending the scope of legal regulation causes changes in the technology, and a widespread deployment and use of these technologies to exercise certain rights which have been threatened by anti-piracy laws.